Gambaran Kecenderungan Gangguan Kecemasan Pada Warga Binaan Pemasyarakatan (WBP) Lapas Perempuan Di Kota “X” - Qonita Salsabila; Andini, Sri Opera Dwi; Purnama, Rezka; Fadhilah, Fadhilah (Jurnal Ekonomika Dan Bisnis (JEBS), 2024)
Psychological problems experienced by prisoners have recently become a special concern. The most common psychological problem is anxiety. The purpose of this study was to determine the description of anxiety experienced by WBP at the Women's Correctional Institution in X City. The research method used in this study is a qualitative method with a phenomenological approach through semi-structured interviews and observation. This research was conducted on three WBPs at the Women's Correctional Institution in X City. The results showed that the subject's anxiety was caused by various factors, such as concerns about family, economic pressure, social stigma, childhood trauma, and experiences in the prison environment. Subject RS experienced anxiety related to his children's views of him and family economic pressure, especially because he was the only breadwinner before becoming a prisoner. Subject P experienced anxiety stemming from the prison environment, social pressure, and fear of the future after release from prison, including community acceptance and decision-making ability. While subject NO showed symptoms of high anxiety stemming from a combination of traumatic experiences while in prison, pressure from the social environment, and feelings of helplessness that affected his mental state. This symptom was characterized by suicide attempts as a manifestation of his anxiety.